1999
DOI: 10.1111/j.1471-0528.1999.tb08304.x
|View full text |Cite
|
Sign up to set email alerts
|

Routine antenatal Rhesus D immunoglobulin prophylaxis: the results of a prospective 10 year study

Abstract: Objective To assess the clinical and financial impact, and identify the problems, of providing routine antenatal RhD immunoglobulin prophylaxis for Rhesus D negative nulliparae.Design A retrospective (198G1986) and prospective (1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996) comparison between two similar populations, one population with nulliparae offered routine RhD immunoglobulin 500 IU prophylaxis at 28 and 34 weeks of gestation part way through the study period, and the other population not of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 23 publications
2
96
1
2
Order By: Relevance
“…Despite these observations, there is convincing evidence that antenatal anti-D prophylaxis given as a single injection at 28 weeks of gestation, intramuscularly 1,2 or intravenously 3 or as two injections at 28 and 34 weeks of gestation respectively, 4,6,18 significantly reduces the incidence of unprovoked antenatal sensitisation. This suggests that the WHO guidance for the minimal residual amount of antibody at 25 mg in the maternal circulation 12 weeks after the first injection is higher than is therapeutically necessary.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite these observations, there is convincing evidence that antenatal anti-D prophylaxis given as a single injection at 28 weeks of gestation, intramuscularly 1,2 or intravenously 3 or as two injections at 28 and 34 weeks of gestation respectively, 4,6,18 significantly reduces the incidence of unprovoked antenatal sensitisation. This suggests that the WHO guidance for the minimal residual amount of antibody at 25 mg in the maternal circulation 12 weeks after the first injection is higher than is therapeutically necessary.…”
Section: Discussionmentioning
confidence: 92%
“…While comparisons between different studies must always be viewed with caution, due to different methodologies, it is evident that a majority of women do not have levels of IgG remaining in their circulation that are thought to be necessary to provide protection at 40 weeks of gestation. Because the administration of antenatal prophylaxis cannot be guaranteed to be given at the precise recommended gestation, and because a large proportion of women deliver beyond the expected date of confinement, 6 the proportion of women with apparently inadequate protection is quite considerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Prevalence of Rh-D alloimmunisation from different centres had a wide range from 0.8% to 4.0% and one study conducted in the same setting reported a frequency of 3.12%. 41,42,43,44 While independent 't' test was performed between ABO and Rh-D HDFN assemblies there was no significant difference regarding maternal age, duration of treatment and duration of stay in ICU. Regarding cord blood haemoglobin and bilirubin levels, there was significant difference in mean values in ABO and Rh-D HDFN cases.…”
Section: Discussionmentioning
confidence: 99%
“…Such routine prophylaxis for nulliparous women signifi cantly reduces the incidence of sensitized next pregnancies with consequent savings, and its adoption nationwide should be encouraged. Improvement in the uptake of prophylaxis is needed, and alternative administration strategies should be explored [14] .…”
Section: Discussionmentioning
confidence: 99%